2016
DOI: 10.1111/1755-5922.12213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fixed‐dose combinations of ezetimibe plus rosuvastatin in patients with primary hypercholesterolemia: MRS‐ROZE (Multicenter Randomized Study of ROsuvastatin and eZEtimibe)

Abstract: SummaryAimWe aimed to compare the effects of fixed‐dose combinations of ezetimibe plus rosuvastatin to rosuvastatin alone in patients with primary hypercholesterolemia, including a subgroup analysis of patients with diabetes mellitus (DM) or metabolic syndrome (MetS).MethodThis multicenter eight‐week randomized double‐blind phase III study evaluated the safety and efficacy of fixed‐dose combinations of ezetimibe 10 mg plus rosuvastatin, compared with rosuvastatin alone in patients with primary hypercholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 44 publications
(80 reference statements)
2
38
0
11
Order By: Relevance
“…Volume 40 Number 2 which was consistent with previous studies. [28][29][30] Another study also found greater LDL-C-lowering efficacy and similar safety profiles of rosuvastatin 5 or 10 mg combined with ezetimibe than those of rosuvastatin 10 or 20 mg monotherapy. 31 In previous research, administration of ezetimibe and rosuvastatin increased the target LDL-C goal from 67% to 96%.…”
Section: Clinical Therapeutics 238mentioning
confidence: 82%
“…Volume 40 Number 2 which was consistent with previous studies. [28][29][30] Another study also found greater LDL-C-lowering efficacy and similar safety profiles of rosuvastatin 5 or 10 mg combined with ezetimibe than those of rosuvastatin 10 or 20 mg monotherapy. 31 In previous research, administration of ezetimibe and rosuvastatin increased the target LDL-C goal from 67% to 96%.…”
Section: Clinical Therapeutics 238mentioning
confidence: 82%
“…However, considering the lower dose of our study protocol, achieving ≥50% reduction in LDL cholesterol in almost half of the study subjects might be considered acceptable. Moreover, it should be considered that increasing the dose of the statin contributes a limited additional reduction rate and may result in a higher rate of side effects [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…A few clinical studies were conducted in Japan, and the reduction rates of LDL cholesterol with rosuvastatin 10 mg were 49.2% [26] and 49.7% [27], which were similar to our study. In Korea, our group recently reported the LDL reduction rate with rosuvastatin 10 mg of 52% [24]. However, the study population of these studies were subjects with familial hypercholesterolemia [26] or hyper LDL cholesterolemia [27], not subjects within the four statin benefit groups as defined by the ACC/AHA guideline.…”
Section: Discussionmentioning
confidence: 99%
“…The number of prevalent patients on ezetimibe increased over time, and the majority of use was ezetimibe added to a statin. 25,26 There was an increase in the use of ezetimibe and statin fixed combinations without the expected decrease in the concomitant use of individual agents.…”
Section: Underreporting Rates For Voluntary Ae Reports Have Been Estimentioning
confidence: 99%